The development of a biological ontology based on a possible connection between EEG and breast cancer using bibliographic reasoning. (2017) - Poulos, Marios
This paper describes, using bibliographic reasoning, a biological ontology based on a possible connection between EEG and breast cancer. The paper uses a data mining approach, applied to PubMed articles. The proposed system will be able to identify the appearance of each gene's ID and compare the coexistence of two genes or proteins in PubMed articles/papers using as queries specific authorised terms. The produced connections (genes and proteins) could be a useful tool for scientists and medical professionals searching for a possible relationship between disorders such as cancer and EEG.